Escaping paternalism : rationality, behavioral economics, and public policy - Rizzo, Mario J.; Whitman, Glen (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2020)
The burgeoning field of behavioral economics has produced a new set of justifications for paternalism. This book challenges behavioral paternalism on multiple levels, from the abstract and conceptual to the pragmatic and applied. Behavioral paternalism relies on a needlessly restrictive definition of rational behavior. It neglects nonstandard preferences, experimentation, and self-discovery. It relies on behavioral research that is often incomplete and unreliable. It demands a level of knowledge from policymakers that they cannot reasonably obtain. It assumes a political process largely immune to the effects of ignorance, irrationality, and the influence of special interests and moralists. Overall, behavioral paternalism underestimates the capacity of people to solve their own problems, while overestimating the ability of experts and policymakers to design beneficial interventions. The authors argue instead for a more inclusive theory of rationality in economic policymaking.
Title from publisher's bibliographic system (viewed on 18 Dec 2019).
Keywords: Economics -- Psychological aspects; Rational choice theory; Paternalism -- Economic aspects